Influence of serum folic acid levels on plasma homocysteine concentrations in patients with rheumatoid arthritis - ÜSTAY, ÖZLEM; DİRESKENELİ, RAFİ HANER (SPRINGER, 2006)
The purpose of this study was to investigate whether negative effects of methotrexate (mtx) on blood homocysteine (hmc) levels can be prevented with the replacement of folic acid. 42 female patients with rheumatoid arthritis (RA) were studied. Patients were separated into two groups according to their treatment status with mtx (group I: 27 patients taking mtx and folic acid; group II: 15 patients not using mtx). The level of hmc was found to be 6.3 +/- 2.4 mu mol/l in group I and 7.87 +/- 3.2 mu mol/l in group II (p > 0.05). Folic acid levels of group I and II were found to be 21.3 +/- 15.9 ng/ml and 8.41 +/- 2.86 ng/ml respectively (p < 0.001). There was a statistically-significant correlation between age and hmc levels (r=0.386, p=0.012). Negative statistically-significant correlations were observed between folic acid and hmc levels. The effects of mtx on hmc can be prevented with the replacement of folic acid.
Keywords: rheumatoid arthritis; methotrexate; homocysteine; folic acid; CARDIOVASCULAR-DISEASE; METHOTREXATE; MORTALITY; HYPERHOMOCYSTEINEMIA; WOMEN